Implementasi Pembelajaraan Kooperatif Tipe Talking Stick Terhadap Hasil Belajar Matematika Siswa Kelas VII - Faisal Batennie (CENDEKIA: JURNAL ILMIAH PENDIDIKAN, 2020)
This study aims to describe the learning outcomes by measuring differences in cognitive learning outcomes of students by using a cooperative learning model Type Talking Stick in class VII Mts. Darul Ulum Kotabaru Academic Year 2018/2019. The research method used is quantitative research that is collecting analysis, and presenting data with observation techniques, questionnaires, and tests of student ability. Student learning outcomes before the application of the Talking Stick learning model, with an average pretest data collection 64.93 Then the learning outcomes after the application of the Talking Stick learning model posttest data acquisition averaged 86.27. There is a difference in better results. Keywords: Implementation, Learning, Talking Stick